GOYANG DANGDUT DAN REPRESENTASI IDEOLOGI DI TELEVISI - Agus Rianto (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2013)
As a genre of popular music, dangdut is part of pop culture entertainment industry.Dangdut has a